2016
DOI: 10.3389/fpsyg.2015.01935
|View full text |Cite
|
Sign up to set email alerts
|

Approach and Withdrawal Tendencies during Written Word Processing: Effects of Task, Emotional Valence, and Emotional Arousal

Abstract: The affective dimensions of emotional valence and emotional arousal affect processing of verbal and pictorial stimuli. Traditional emotional theories assume a linear relationship between these dimensions, with valence determining the direction of a behavior (approach vs. withdrawal) and arousal its intensity or strength. In contrast, according to the valence-arousal conflict theory, both dimensions are interactively related: positive valence and low arousal (PL) are associated with an implicit tendency to appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…To this aim, we compared FFA and brain oscillations elicited by words denoting concepts associated with approach responses (i.e., anger words) with those evoked by words with conceptual referents related to conflicting action tendencies such as escape, fight of freeze (i.e., fear words). In line with prior reports, our data suggest a contribution of motivational systems to the processing of emotion words ( Citron et al, 2014 , 2016 ; Wang et al, 2018 ). As expected, participants gave distancing responses in the “approaching-distancing” task to both fear and anger negative words, whereas approaching responses were mainly restricted to positive words.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To this aim, we compared FFA and brain oscillations elicited by words denoting concepts associated with approach responses (i.e., anger words) with those evoked by words with conceptual referents related to conflicting action tendencies such as escape, fight of freeze (i.e., fear words). In line with prior reports, our data suggest a contribution of motivational systems to the processing of emotion words ( Citron et al, 2014 , 2016 ; Wang et al, 2018 ). As expected, participants gave distancing responses in the “approaching-distancing” task to both fear and anger negative words, whereas approaching responses were mainly restricted to positive words.…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, the valence-arousal conflict theory ( Robinson et al, 2004 ) predicts that positive valence and low arousal are associated with approach-related action tendencies, while negative valence and high arousal are linked to avoidance behaviors. In line with this proposal, prior studies have shown that motivationally incongruent words (e.g., positive high arousing and negative low arousing words) are responded to more slowly than motivationally congruent ones (positive low arousing and negative high arousing words), although these effects were restricted to tasks that explicitly demanded approach-avoidance judgments from participants ( Citron et al, 2014 , 2016 ; Wang et al, 2018 ). Of note, in these studies the contribution of motivational directions to the processing of emotional words is subsidiary of the two affective dimensions of valence and arousal.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Regarding the processing of single words, rapid serial presentation of words with emotional content, in several studies, facilitated both initial stimulus processing in the visual cortex and subsequent recall performance of emotional words (e.g., Kissler et al, 2007 ; Herbert et al, 2008 ). Moreover, in several studies, reading emotional words activated emotional brain structures such as the amygdala ( Hamann, 2001 ; Tabert et al, 2001 ; Kuchinke et al, 2005 ; Hazlett et al, 2007 ; Herbert et al, 2009 ) and induced changes in affective behavior including priming of approach and avoidance including defensive responses like the startle-reflex (e.g., Herbert et al, 2006 ; Herbert and Kissler, 2010 ; Citron et al, 2016 ). Presentation of emotional words also influences the perception and appraisal of non-verbal emotional signals: on a behavioral (e.g., Lindquist et al, 2006 ) as well as on a neural or physiological level ( Lieberman et al, 2007 ; Moseley et al, 2012 ; Herbert et al, 2013a , c ), having implications for the treatment of clinical and neurological disorders ( Roberson et al, 2007 ; Kircanski et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, positive emotions are generally correlated with approach tendencies, whereas negative emotions are linked to withdrawal/avoidance tendencies (e.g., Roseman, 2008). Although such action tendencies have been scarcely investigated when the emotional stimuli are words, a few studies suggest that they may have also a role in word processing (e.g., Citron et al, 2016;Huete-Pérez et al, 2019). The congruency/incongruency between the action tendencies associated with the distinct meanings of ambiguous words might account for the present findings.…”
Section: Discussionmentioning
confidence: 52%